PENGARUH CITRA MEREK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA BISNIS FRANCHISE MINUMAN - Yunita Fitri Wahyuningtyas (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This research is conducted upon the emergence of many companies producing the same product of the same kind and function. It leads to the urgency of proper and well planned marketing strategy. This research aims to investigate how far the influence of branding, product quality, and price toward consumer’s satisfaction in beverage franchise business. This research utilizes 5 likert scale questionnaire which is tested by using multiple regression analysis to reveal whether or not there is partial and simultaneous influence of branding, product quality, and price toward consumer’s satisfaction in beverage franchise business. Sampling method is accidental sampling technique, in which sample of particular population is taken based on the accessibility and availability of the sample during the sampling process. Sample used is 100 samples among consumers or customers of Mang Endy Milkshake. The result shows that branding, product quality, and price influence consumer’s satisfaction in beverage franchise business.